HW9_prob4(a)_GPS3_G7

# HW9_prob4(a)_GPS3_G7 - d L dt = N . (9) Next, take the dot...

This preview shows pages 1–2. Sign up to view the full content.

Problem GPS 5.3 (2 nd ed. 5-7) We have a collection of mass points rotating about a f xed point, and the positions r i and velocities v i of these points are measured in a space f xed, inertial frame whose origin is at the f xed point. Start with the de f nition of T T = 1 2 X i m i v i · v i , (1) and take a total time derivative (in the inertial, space f xed frame, naturally) to f nd dT dt = X i m i d v i dt · v i . (2) Next, we f rst note from Newton’s Second Law that m i d v i dt = F i , (3) where F i is the force on mass point i , and we also express the velocity of point i in terms of the angular velocity vector ω as v i = d r i dt = ω × r i , (4) because in the rotating frame ( d r i /dt ) b =0 for all points of a rigid body. After substituting Eqs.(3) and (4) into (2) we f nd dT dt = X i F i · ( ω × r i ) , (5) which we cyclically permute to obtain dT dt = X i ω · ( r i × F i ) . (6) Recognizing that the total torque on the rigid body is N = X i ( r i × F i ) , (7) we f nally obtain the desired result dT dt = ω · N . (8) 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Alternate derivation: Start with the fundamental equation governing the rate of change of angular momentum from Chapter 1 or Chapter 5
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: d L dt = N . (9) Next, take the dot product of Eq.(9) with ω to get ω · d L dt = ω · N . (10) Now use the rate of change of a vector formula to rewrite the left dot product of Eq.(10) as ω · d L dt = ω · μ d L dt ¶ b + ω · ( ω × L ) , (11) and recognize that ω · ( ω × L ) = . Then, express ω and L as vectors in the principal axis body frame (with constant values of the principal moments I 1 , I 2 , and I 3 ) to expand the dot product as ω · μ d L dt ¶ b = ( ω 1 I 1 dω 1 dt + ω 2 I 2 dω 2 dt + ω 3 I 3 dω 3 dt ) = 1 2 d dt ( I 1 ω 2 1 + I 2 ω 2 2 + I 3 ω 2 3 ) = dT dt , (12) and obtain the desired result, dT dt = ω · N . (13) The distinction between a space frame and body frame derivative in the f nal equation is super F uous because T is a scalar. 2...
View Full Document

## This note was uploaded on 12/19/2010 for the course PHYSICS ph 409 taught by Professor Wilemski during the Fall '10 term at Missouri S&T.

### Page1 / 2

HW9_prob4(a)_GPS3_G7 - d L dt = N . (9) Next, take the dot...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online